Human errors self-reported by automobilists from bahia blanca, Argentina - Buedo, Paola; Silberman, Pedro; Mujica, Daiana (Revista Chilena de Salud Pública, 2017)
Objective: To describe the types of errors reported by drivers who commuted in the city of Bahia Blanca between September 2014 and April 2015. Method: Quantitative descriptive cross-sectional study. A convenience sample was defined, and a structured digital survey, based on the Spanish-translated version of the “Driver Behaviour Questionnaire”, was constructed and then validated using the Delphi method. Data were analyzed with SPSS statistical software. Results: Of the automobilists surveyed, 30% reported having nearly colliding with a bicycle or motorcycle while making a turn; 36.3% said they have had to brake suddenly to avoid a collision because they were distracted and did not realize the vehicle in front of them had slowed down; and 25.3% had forgotten to use the turn signal before turning or changing lanes. In addition, only 80-2% of respondents always wear a seat belt; 11-4% do not respect red lights; 43.9% use their phones while driving; and 22.9% admit driving while intoxicated over the legal alcohol limit. Finally, 38% report being impatient and accelerating out of a traffic light, while 62.7% have riskily passed a slower vehicle, due to impatience. Conclusions: Driving an automobile is a complex situation that requires multiple skills and, most fundamentally, a sense of respect and solidarity with other drivers, coupled with punitive control of serious yet preventable human errors.